PERFORMANCE ANALYSIS WITH EMPLOYEE WORK DISCIPLINE AS AN INTERVENING VARIABLE (CASE STUDY ON MILLENNIAL EMPLOYEES AT PDAM TIRTA MOEDAL SEMARANG CITY) - Yulianti, Shinta; Sumastuti, Efriyani; Prabowo, Heri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is analyze the influence of the work environment, motivation, workload, and work stress on employee performance through work discipline as an intervening variable. The samples in this study was 163 respondents who mineral employees of PDAM Tirta Moedal. The sampling technique used random sampling. The data collection technique used the survey method using a questionnaire. The method used PLS with the SmartPLS application. The research findings produced were that the work environment influenced work discipline, motivation influenced work discipline, workload influenced work discipline, work stress did not influence discipline, work discipline influenced performance, the environment did not influence performance, motivation did not influence performance, workload influenced performance, work stress did not influence performance, discipline did not mediate the environment on performance, discipline did not mediate motivation on performance, discipline did not mediate workload on performance, and discipline did not mediate work stress on performance.